Molecular mechanisms of migraine? - Ramagopalan, S; Ramscar, N; Cader, M (2007)
Migraine is a common debilitating neurological disease characterised by attacks of severe headache with or without preceding aura. Its aetiology remains elusive; however it is clear that an interplay of genetic and environmental components play an important role. Familial hemiplegic migraine (FHM) is a rare and severe variant of migraine with aura and follows an autosomal dominant pattern of inheritance. This disease is genetically heterogeneous,with three causative genes having been identified. This review uses insights garnered from FHM to try and shed light on possible migraine disease pathogenesis.